2023
DOI: 10.3390/polym15132786
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposites with Optimized Polytetrafluoroethylene Content as a Reinforcement Agent in PA12 and PLA for Material Extrusion Additive Manufacturing

Nectarios Vidakis,
Markos Petousis,
Amalia Moutsopoulou
et al.

Abstract: Herein, polytetrafluoroethylene (PTFE) is evaluated as a reinforcement agent in material extrusion (MEX) additive manufacturing (AM), aiming to develop nanocomposites with enhanced mechanical performance. Loadings up to 4.0 wt.% were introduced as fillers of polylactic acid (PLA) and polyamide 12 (PA12) matrices. Filaments for MEX AM were prepared to produce corresponding 3D-printed samples. For the thorough characterization of the nanocomposites, a series of standardized mechanical tests were followed, along … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 81 publications
(90 reference statements)
0
4
0
Order By: Relevance
“…However, the results obtained in this research work showed that, for the release of the PUR on these two materials, the impact of the degree of surface roughness is minimal compared to the effect caused by the progressive loss of the RA on the mold surface and the degradation that the isocyanate causes as consecutive molding/demolding cycles are applied. Along with this, other recent works have been assessed solutions based on FFF technique for fast prototyping with so diverse part materials such as resins, ethylene vinyl acetate (EVA) or alumina-based ceramics (Bere et al, 2020;Gohn et al, 2022;Li et al, 2015;Wick-Joliat et al, 2021). The results of all these works confirmed the great importance of the application of diverse treatments for the surface finish of the manufactured molds to avoid the appearance of the printing lines typical of the FFF technique on the surface of the molded product.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…However, the results obtained in this research work showed that, for the release of the PUR on these two materials, the impact of the degree of surface roughness is minimal compared to the effect caused by the progressive loss of the RA on the mold surface and the degradation that the isocyanate causes as consecutive molding/demolding cycles are applied. Along with this, other recent works have been assessed solutions based on FFF technique for fast prototyping with so diverse part materials such as resins, ethylene vinyl acetate (EVA) or alumina-based ceramics (Bere et al, 2020;Gohn et al, 2022;Li et al, 2015;Wick-Joliat et al, 2021). The results of all these works confirmed the great importance of the application of diverse treatments for the surface finish of the manufactured molds to avoid the appearance of the printing lines typical of the FFF technique on the surface of the molded product.…”
Section: Introductionmentioning
confidence: 77%
“…Among them, the PFA allowed 1,500 PUR foam molding/demolding cycles run without incident. Despite the excellent results that these fluoropolymers have shown in their behavior with PUR foam, they cannot be used as a filament in FFF 3D printing due to their high extrusion temperature and the impossibility of adhesion between layers, in addition to the fact that it is very difficult to obtain pure PTFE filament, but there are advanced filaments that includes it as filler additive for nonsticking purposes (Rajakaruna et al , 2022; Vidakis et al , 2023). Nevertheless, the formation of toxic fumes that would be generated from this material when melted using fused deposition technology should not be omitted either (Sajid and Ilyas, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Despite being a non- The filament is guided through the heating zone to successfully melt the polymer and extrude through a nozzle (printing head) [50]. The extruded material is then lined up as per the pre-program onto a printing bed (base) on a layer-by-layer basis [51]. The printing temperature can be higher than the melting temperature of the thermoplastic to maintain a consistent flow of melts [42].…”
Section: Fdm Filamentsmentioning
confidence: 99%
“…In the MEX method, a thermoplastic filament is guided through a heated nozzle that moves in horizontal and vertical directions as per a pre-planned design. The molten filament extrudes on a print bed in a controlled manner through the nozzle to produce the final material [ 12 ].…”
Section: Introductionmentioning
confidence: 99%